2005
DOI: 10.1128/jvi.79.2.1045-1052.2005
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Acceleration or Prevention by a Coxsackievirus B4 Infection: Critical Requirements for both Interleukin-4 and Gamma Interferon

Abstract: Type 1 diabetes acceleration in nonobese diabetic (NOD) mice through coxsackievirus B4 (CVB4) infection requires a preexisting critical mass of autoreactive T cells in pancreatic islets

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
47
1
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(54 citation statements)
references
References 32 publications
4
47
1
1
Order By: Relevance
“…Prevention of lethal CVB1 infection by a prior CVB3 infection has also been observed in a mouse model, fitting nicely with the findings in the current study (38). In addition to crossprotection, other mechanisms related to the induction of b-cell tolerance may mediate the protective effect of viruses against type 1 diabetes as described in NOD mice (39,40). In both cases, the close relationship between the protective and the diabetogenic serotypes suggests a particular impact of the CVB group enteroviruses on the risk of diabetes.…”
Section: Discussionsupporting
confidence: 76%
“…Prevention of lethal CVB1 infection by a prior CVB3 infection has also been observed in a mouse model, fitting nicely with the findings in the current study (38). In addition to crossprotection, other mechanisms related to the induction of b-cell tolerance may mediate the protective effect of viruses against type 1 diabetes as described in NOD mice (39,40). In both cases, the close relationship between the protective and the diabetogenic serotypes suggests a particular impact of the CVB group enteroviruses on the risk of diabetes.…”
Section: Discussionsupporting
confidence: 76%
“…Diabetes development after enterovirus infection in the most commonly used experimental model, the NOD mouse, is dependent on the already established prediabetic phase including insulitis [15][16][17]31], which in the NOD mouse occurs after maternally transferred antibodies may have waned [32]. This is in contrast with humans in whom islet autoantibodies may already appear before the disappearance of maternal antibodies [23,33,34].…”
Section: Discussioncontrasting
confidence: 42%
“…[6,12]). Furthermore, experimental animal models have indicated that enterovirus infections can cause direct beta cell damage [13,14] and alter disease progression in the NOD mouse model [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…All samples, including those showing negative results for CVB4 E2 RNA, were positive for GAPDH mRNA, proving the RNA integrity and the absence of reaction inhibitors (results not shown). Our data show that a systemic spreading of CVB4 E2 following oral inoculation is possible and that outbred mice, in addition to inbred, diabetic, immuno-compromised or transgenic mice (4,8,9,11,18,21), can be infected with that viral strain. The natural expression in the mouse of a coxsackievirus and adenovirus receptor strongly homologous to the human one (19), made possible the use of these animals as models to study the infection with CVB4 E2.…”
mentioning
confidence: 98%